The Nata de Coco Quality Analysis for Making Fiber-Rich Instant Drink Powder - Natalia Peni; Melania Priska (CHEMICA: Jurnal Teknik Kimia, 2021)
One of the potentials of coconut water that is widely developed in Indonesia is nata de coco. Nata de coco is the result of the fermentation of coconut water which is added by Acetobacter xylum. The research aim was to determine the quality of nata de coco as the basic material for making instant drink powder (IDP) which consists of natural flavors of orange, mango, and soursop. The step of the research was making a starter, making nata de coco, making IDP, and testing the quality of IDP (water content, specific gravity, taste, water solubility, and fiber). Data were analyzed using Tukey's significant difference test with a significance of 0.05%. The results showed that the water content of the IDP three flavors was less than 3%. Mango specific gratify is also higher but the orange flavor is the one of taste that people really like. The level of solubility in water shows that soursop is higher solubility. The fiber content of IDP orange is higher than mango and soursop. Therefore, nata de coco can be used as a raw material for making IDP.